1996
DOI: 10.1007/s002040050359
|View full text |Cite
|
Sign up to set email alerts
|

A convenient method to discriminate between cytochrome P450 enzymes and flavin-containing monooxygenases in human liver microsomes

Abstract: Liver microsomes are a frequently used probe to investigate the phase I metabolism of xenobiotics in vitro. Structures containing nucleophilic hetero-atoms are possible substrates for cytochrome P450 enzymes (P450) and flavin-containing monooxygenases (FMO). Both enzymes are located in the endoplasmatic reticulum of hepatocytes and both need oxygen and NADPH as cofactors. The common method to distinguish between the two enzyme systems is to use the thermal inactivation of FMO and to inhibit P450 completely wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…This strongly suggests that the heat lability observed for human liver FMO is a consistent characteristic in other preclinical species, and heat lability is a useful and general method for differentiating between FMO and P450 in microsomal incubations. This is used routinely for human liver microsomes (Grothusen et al, 1996), and has been reported for rat, mouse, and cow (Kedderis and Rickert, 1985;Venkatesh et al, 1992;Blake et al, 1995;Ring et al, 1999;Santi et al, 2002). We extend this analysis here for other traditional preclinical species (i.e., dog and monkey).…”
Section: Fisher Et Almentioning
confidence: 84%
See 1 more Smart Citation
“…This strongly suggests that the heat lability observed for human liver FMO is a consistent characteristic in other preclinical species, and heat lability is a useful and general method for differentiating between FMO and P450 in microsomal incubations. This is used routinely for human liver microsomes (Grothusen et al, 1996), and has been reported for rat, mouse, and cow (Kedderis and Rickert, 1985;Venkatesh et al, 1992;Blake et al, 1995;Ring et al, 1999;Santi et al, 2002). We extend this analysis here for other traditional preclinical species (i.e., dog and monkey).…”
Section: Fisher Et Almentioning
confidence: 84%
“…Human FMOs are characterized by heat lability in the absence of NADPH, and this property is often exploited to elucidate the enzyme involvement in a particular oxidation (Rettie et al, 1995). For example, preheating microsomes at 45 or 50°C for 1 to 3 min in the absence of NADPH is a common method for inhibiting FMO activity (Grothusen et al, 1996), and this inhibition is prevented in the presence of cofactor. Thus, prewarming of microsomes during a typical metabolic lability experiment in the absence of NADPH, which occurs when the incubation is initiated with cofactor, may have profound effects on the FMO activity and could potentially compromise the in vitro to in vivo scaling of FMOmediated reactions.…”
mentioning
confidence: 99%
“…A role for flavin-containing monooxygenases was anticipated based on their known ability to catalyze N-oxidation reactions (Cashman, 1995). This hypothesis was first investigated using the heat lability of FMOs compared with P450s in human liver microsomes (Grothusen et al, 1996). It was found that preincubation of human liver microsomes at 50°C for 2 min (to inactivate FMOs) inhibited VRT-750074 formation by 44 Ϯ 5% (1 M MK-0457) and 66 Ϯ 4% (10 M MK-0457), whereas VRT-171335 formation was not significantly altered by the same treatment.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…The oxidizing activity that produces the sulfoxide appears to be exhibited by both CYPs and FMOs in rats and humans. Human BZF: bezafibrate,SP: 3,phenol, SOP: 3,5-dimethyl-4-(methylsulfonyl)phenol FMO1 was found to contribute to the sulfoxidation of aldicarb, ethiofencarb, and methiocarb (Grothusen et al, 1996;Schlenk et al, 2002;Furnes and Schlenk, 2005). Usmani et al (2004) have shown the involvement of human CYP2C and FMO1 in methiocarb sulfoxidation.…”
Section: Discussionmentioning
confidence: 95%